Epidemiology and Drug Resistance of Fracture-Related Infection of the Long Bones of the Extremities: A Retrospective Study at the Largest Trauma Center in Southwest China - Zhang, Zhengdong; Liu, Pan; Wang, Wenzhao; Wang, Shanxi; Li, Bohua; Li, Jun; Yang, Banyin; Li, Mingxin; Li, Qin; Yang, Hai; Huang, Zeyu; Liu, Lei (Frontiers in Microbiology, 2022)
Objective To describe the demographic characteristics, risk factors, and bacterial resistance of fracture-related infection (FRI) of the long bones of the extremities. Materials and Methods This single-center study retrospectively evaluated patients with FRI of the long bones of the extremities at West China Hospital between January 2012 and December 2017, and analyzed the demographic characteristics, risk factors, distribution of pathogenic bacteria, and bacterial drug resistance. Results Among 9,900 patients, 535 patients (5.4%) were diagnosed with FRI. The most common site of FRI was tibiofibular (298, 55.7%), with 424 cases (79.2%) of open fractures, and 282 cases (52.7%) due to traffic injuries. The 41–50 years age group had the highest incidence of FRI with 157 (29.3%) cases. Overall, 546 strains of 52 types of bacteria were detected in FRI patients, with 105 strains of multidrug-resistant (MDR) bacteria. Methicillin-resistant Staphylococcus aureus (48, 8.8%) and extended-spectrum-β-lactamase Escherichia coli (32, 5.8%) accounted for the largest proportion. Multivariate logistic regression analysis showed that sex (odds ratio [OR] 1.813; 95% confidence interval [CI], 1.071∼3.070; P = 0.027) and fracture type (OR 3.128; 95% CI, 1.683∼5.815; P < 0.001) were independent risk factors for monomicrobial infection (MI). Female sex (OR 4.190; 95% CI, 1.212∼14.486; P = 0.024) was an independent risk factor for polymicrobial infection (PI). Conclusion This study clarified the infection rates, changes in the bacterial spectrum, and drug resistance characteristics, and risk factors of FRI of the long bones of the extremities in the largest trauma center in southwest China.